Casein micelle structure: Models and muddles - Horne, David S. (Current opinion in colloid & interface science, 2006)
Various models of the assembly and structure of the casein micelle are critically reviewed. The subunit and Holt models are revealed to be products of muddled thinking and subject to rigid constraints and restrictions, or in the case of the Holt model guilty of serious omission. Both are shown to be particular cases of the dual-binding model when these restrictions are lifted and the omissions made good.